Japanese growth and stagnation: A Keynesian perspective - Takeshi Nakatani; Peter Skott (University of Massachusetts, Department of Economics, 2006)
This paper uses a modi.ed Harrodian model to understand both the long period of rapid Japanese growth and the recent period of stagnation. The model has multiple steady-growth solutions when the labour supply is highly elastic, and government intervention, we argue, took the Japanese economy onto a high-growth trajectory. Labour constraints began to appear around 1970, and a combination of high saving rates and slow population growth account for the stagnation of the 1990s. This combination produces a structural liquidity trap and threatens the sustainability of attempts to ensure near full employment through fiscal policy or by running a persistent trade surplus.
Keywords: E12; E63; O53; 330; Japan; growth; stagnation; liquidity trap; public debt; multiple equilibria; Wirtschaftswachstum; Stagnation; Liquiditätspräferenz; Öffentliche Schulden; Japan